2018
DOI: 10.1080/01652176.2018.1519321
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, virulence genotype and antimicrobial resistance of uropathogenic Escherichia coli (UPEC) isolated from sows

Abstract: Background: Urinary tract infections (UTI) cause severe losses to the swine industry worldwide and uropathogenic Escherichia coli (UPEC) are the main agent isolated from UTI in sows.Objective: The aim of this study was to investigate the virulence genes, assess the phylogenetic background, clonal diversity, and the pattern of resistance to antimicrobials in 186 isolates of UPEC isolated from sows in Brazil.Materials and methods: Urine samples from 300 sows of three herds with clinical signs from São Paulo Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 36 publications
3
10
0
1
Order By: Relevance
“…In the current study, 98% of the UPEC isolates were multidrug-resistant. This finding was consistent with those reported by Spindola et al [ 13 ] and Rehman et al [ 14 ], but differed from reports by Navidinia et al (26%) [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, 98% of the UPEC isolates were multidrug-resistant. This finding was consistent with those reported by Spindola et al [ 13 ] and Rehman et al [ 14 ], but differed from reports by Navidinia et al (26%) [ 15 ].…”
Section: Discussionsupporting
confidence: 92%
“…The probability of expression of type 1 and P fimbriae resulting from the presence of the complete operons was significantly higher in isolates from piglets. Recently, ExPEC infections have become more common in the pig industry [25][26][27], so it is important to understand the population structure of porcine commensal E. coli. We should also be aware of the reservoir of VGs carried by commensal E. coli from pigs in terms of the public health threat.…”
Section: Discussionmentioning
confidence: 99%
“…Infections caused by ExPEC strains occur worldwide and are associated with great economic cost [24]. ExPEC is an important pathogen in the swine industry, in several countries, responsible for substantial economic losses [25][26][27]. Porcine ExPEC is an important pathogen causing UTI-a significant cause of death in adult animals [6].…”
Section: Introductionmentioning
confidence: 99%
“…More than 80% of these isolates were resistant to sulfonamides (94.6%), tetracycline (91.9%), and florfenicol (83.3%); 50% to 70% of the isolates were reported as resistant to nalidixic acid (66.1%), sulfamethoxazole-trimethoprim (59.6%) and streptomycin (52.6%). Resistance frequencies lower than 25% were detected to ciprofloxacin (22.5%), spectinomycin (11.2%), and gentamycin (2.6%) [86]. In contrast, Silva et al reported eight isolates obtained in 2012 also in the same state from pig fecal swabs resistant to third-and fourth-generation cephalosporins, associated with the occurrence of the ESBL encoding gene bla CTX-M-15 .…”
Section: E Colimentioning
confidence: 97%